The Role of CSR in SMEs within the International Textile Industry - Zhao, Xiaoyu; Martínez Pantoja, Yadira Ixchel; San José Iglesias, Rafael; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis examined how textile SME owners perceive and apply CSR in their companies' businesses. The case study focuses on China as an example; it is one of the world’s largest textile producers and exporters, and its SMEs form the dominant part of the textile industry. Interviews with senior managers from three Chinese textile SMEs, Hangzhou Tianlong Handbag Co., Ltd., Zhuji Jiayi Knitting Co., Ltd., and Zhuji Furen Group Co., Ltd., were conducted to examine their perceptions of CSR and their CSR implementations. The theoretical framework draws on CSR definitions by Bowen, Carroll (Carroll’s pyramid), and Elkington (Triple Bottom Line), as well as the reports from the United Nations, OECD, International Labour Organization, World Bank, and existing literature on CSR drivers and challenges in SMEs. In addition, the SDGs were also examined as a complementary framework for the CSR analysis. A qualitative case study design was adopted by using semi-structured interviews with senior managers and business owners to find out how they perceive and apply CSR in their businesses. The findings show that CSR awareness and engagement among Chinese SMEs have improved in recent decades, but there is still room for improvement. Limitations include the small sample size and single-industry scope. However, despite these constraints, this thesis contributes practical insights for strengthening CSR awareness and promoting sustainable development in China’s textile SMEs, while also offering a useful reference for SMEs in other countries that face similar situations.
Vedoucí práce: Yadira Ixchel Martínez Pantoja
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses